PENGARUH PENAMBAHAN PUPUK MAJEMUK NPK TERHADAP PERTUMBUHAN DAN KADAR PROTEIN JAMUR TIRAM PUTIH (Pleurotus ostreatus) - imam mahadi; Evi Suryawati; Nurkameria Nurkameria (UIR Press, 2016)
White Oyster Mushrooms (Pleurotus ostreatus) is one foodstuffs favored by the people. This mushrooms demand higher beucase it is tasty and seful to health. The research was conducted to determine the effect of the addition NPK complex fertilizers to the growth and protein content white oyster mushrooms (pleurotus ostreatus). This research using non factorial completely randomized design that consist 5 treatments and 3 replicatesand totally obtain 15 experimental design. It would further DMRT test if effect. The observed parameters include growth and protein content white oyster mushrooms. Based on the results revealed that the addition of NPK effect on all parameters observed where the best dosage is treatment P2 with the addition of NPK 10gr / 1 kg of growing media. The P2 treatment effect on time appears pinhead, pinhead number, stem length and wet weight white oyster mushrooms